Coloration of aluminum pigment using SiO2 and γ-glycidoxypropyltrimethoxysilane with dichlorotriazine reactive dye. Issue 5 (5th September 2016) - Tawiah, Benjamin; Zhang, Liping; Tian, Anli; Fu, Shai Shao
Abstract : Purpose: The purpose of this paper is to colour aluminium pigment to the highest chroma using SiO2 and organic silane with dichlorotriazine reactive dye and investigate its reaction mechanism, chemical stability and thermal properties to improve its applicability in surface coatings. Design/methodology/approach: Aluminium pigment was encapsulated by the catalysed sol-gel method using SiO2, followed by modification with γ-glycidoxypropyltrimethoxysilane (GPTMS). Purified reactive dye (1-Amino-4-[3-(4, 6-dichlorotriazin-2-ylamino)-4-sulfophenylamino]anthraquinone-2-sulfonic acid (X-BR)) was covalently immobilized onto modified SiO2 to obtain coloured aluminium pigment. The reaction mechanism, chemical stability and thermophysical properties were investigated by Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy, X-ray diffraction, scanning electron microscope, transmission electron microscope and thermogravimetric analyses (TGA). Findings: The results showed that X-BR was covalently attached to modified Al/SiO2 with maximum colour grafting of 95 per cent when the dosage of GPTMS and X-BR per weight of modified Al/SiO2 was 25 and 15 per cent, respectively, at pH 8.5 and a temperature of 40°C. The coloured aluminium pigment had good chemical stability with excellent anti-migration properties in many solvents. Research limitations/implications: The organic silane used required a careful control of pH to ensure maximum colour grafting efficiency meanwhile other silanes with amine groups could also be used effectively with different kinds of colorants besides reactive dyes. Practical implications: The method used is less cumbersome and provides a simple route to preparing coloured aluminium pigment. Originality/value: The use of organic-inorganic SiO2 /γ- GPTMS with purified reactive dye to covalently colour aluminium pigment to the highest chroma is novel and will help advance the frontiers of knowledge on coloration of aluminium pigments.